PENGARUH KONFLIK TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DPRD KABUPATEN SIAK - Putra, Eka (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This research was conducted at the DPRD Secretariat Of The Siak Regency. The purpose of this study was to determined the effect of conflict on the performance of employees in the DPRD Secretariat of Siak Regency. The population in this study were 44 people from the DPRD Secretariat Of The Siak Regency. While the number of samples set in this study are all of the population of 44 people. Data analysis using simple linear regression analysis with SPSS 16.00 for Windows. Based on a simple linear regression equation Y = 18,397 + 0,656X. Conflict variables (X) with t count (4,336) > t table (2,018) and probability (0,00) <0,05. Then Ho is rejected and Ha is accepted, meaning that the conflict variable has a positive and significant effect on the performance of the DPRD Secretariat Of The Siak Regency. R-square value can be obtained (coefficient of determination) of 0.309 or 30.9%. This shows that conflict contributes to the performance of the Siak Regency DPRD Secretariat employees by 30.9%, while the remaining 60.1% is influenced by other variables outside the variables in this study. The recommendation given that better to be able to create a conducive atmosphere related to the delegation of tasks from a work unit to another work unit in order to facilitate the performance of employees with measurable to avoid accumulating a job in a work unit. In the other side, employees must know andÂ understand about their task and job desk in order to improve their performance.